Neuropsychiatric perspectives on nodding syndrome in northern Uganda: A case series study and a review of the literature - Musisi, S.; Akena, D.; Nakimuli-Mpungu, E .; Abbo, C.; Okello, J. (African Journals Online (AJOL), 2013)
Background: Nodding Syndrome (NS), previously called Nodding Disease, is a chronic and debilitating illness affecting thousands of children aged 3-18 years in post-conflict Northern Uganda and South Sudan. Characterised by malnutrition, stunted growth, mental retardation and seizures, some researchers have designated it as epilepsy. With reports appearing in Northern Uganda in1997, NS reached epidemic proportions around 2000-2003 when people were moved into Internally Displaced People’s (IDP) camps. Investigations for infections (onchocerciasis) and toxins have been inconclusive as to cause, treatment or outcome. No study has addressed the possible relationship of NS to childhood war-trauma experiences. Objective: To explore a possible relationship of exposure to prolonged war-trauma and the emergence of epidemic NS in Northern Uganda. Method: This study was a case-series descriptive psychiatric naturalistic field observations of NS cases from homesteads in Northern Uganda and psychiatric investigations and treatment of NS cases referred to Mulago National Referral and Teaching Hospital. Results: Detailed Psychiatric clinical evaluations and field observations revealed that NS children had been exposed to severe war-related psychological and physical trauma as well as non-specific CNS insults including untreated CNS infections/infestations and malnutrition possibly causing seizures. Many children suffered post-traumatic stress disorder (PTSD) and depression. Conclusion: NS could present as an association of childhood complex PTSD, (called Developmental Trauma Disorder), occurring in the chronically war-traumatised children of Northern Uganda, complicated by severe prolonged depression with its characteristic symptoms of psychomotor retardation, anxiety, anhedonia and anorexia. This, coupled with food shortages, resulted in malnutrition, wasting and stunted growth with severe avitaminoses. Many children had seizures. All this calls for multi-disciplinary treatment approaches.